Electrochemical exfoliation of graphite in nanofibrillated kenaf cellulose (NFC)/surfactant mixture for the development of conductive paper. (15th January 2020) - Ardyani, Tretya; Mohamed, Azmi; Abu Bakar, Suriani; Sagisaka, Masanobu; Umetsu, Yasushi; Hafiz Mamat, Mohamad; Khairul Ahmad, Mohd; Abdul Khalil, H.P.S.; King, Stephen M.; Rogers, Sarah E.; Eastoe, Julian
Graphical abstract: Highlights: Combinations of commercial surfactants and cellulose were used for exfoliation. A cationic surfactant is a more efficient exfoliant than an anionic surfactant. Six orders of magnitude enhancement in conductivity achieved with cationic type. High conductivity is achieved with a low filler loading (0.05 w/w). Abstract: The effect of incorporating common dodecyl anionic and cationic surfactants such as dodecyltrimethylammonium bromide (DTAB), dodecylethyldimethylammonium bromide (DDAB), and sodium dodecylsulfate (SDS) in nanocomposites of reduced graphene oxide and nanocellulose are described. The stabilization and electrical properties of the nanocomoposites of reduced graphene oxide (RGO) and nanofibrillated kenaf cellulose (NFC) were characterized using four-point probe electrical conductivity measurements. Raman spectroscopy, field emission scanning electron microscopy, and high-resolution transmission electron microscopy were used to investigate dispersion morphology and the quality of RGO inside the NFC matrices. Small-angle neutron scattering (SANS) was used to study the aggregation behavior of the aqueous surfactant systems and RGO dispersions. The cationic surfactant DTAB proved to be the best choice for stabilization of RGO in NFC, giving enhanced electrical conductivity five orders of magnitude higher than the neat NFC. The results highlight the effects of hydrophilic surfactant moieties on the structure, stability and properties of RGO/NFC composites.